2022
DOI: 10.3847/1538-4357/ac6be5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Circumstellar Dust Scattering on the Light Curves and Polarizations of Type Ia Supernovae*

Abstract: Observational signatures of the circumstellar material (CSM) around Type Ia supernovae (SNe Ia) provide a unique perspective on their progenitor systems. The pre-supernova evolution of the SN progenitors may naturally eject CSM in most of the popular scenarios of SN Ia explosions. In this study, we investigate the influence of dust scattering on the light curves and polarizations of SNe Ia. A Monte Carlo method is constructed to numerically solve the process of radiative transfer through the CSM. Three types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the thermonuclear ignition of carbon-oxygen WDs is off-center, suggested by the relationship between the early phase velocity gradient of the ejecta and the late-phase velocity shift of emission lines [61]. The late-phase spectroscopic or photometric observations can also diagnose the existence of circumstellar gas around SNe Ia, or the light echos from interstellar or circumstellar dust [17,62,63].…”
Section: Discovering Bright Sne Iamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the thermonuclear ignition of carbon-oxygen WDs is off-center, suggested by the relationship between the early phase velocity gradient of the ejecta and the late-phase velocity shift of emission lines [61]. The late-phase spectroscopic or photometric observations can also diagnose the existence of circumstellar gas around SNe Ia, or the light echos from interstellar or circumstellar dust [17,62,63].…”
Section: Discovering Bright Sne Iamentioning
confidence: 99%
“…To date, the physical nature of SNe Ia, however, is still elusive, such as the pathway of WDs acquiring mass [1], the region of thermonuclear ignition [15], and the existence of a surviving companion or the circumstellar material (CSM) [16,17]. One efficient way to reveal these mysteries is to capture the multi-band photometric signals of SNe Ia soon after the explosion.…”
Section: Introductionmentioning
confidence: 99%
“…SNe Ia are characterized by the absence of hydrogen and the presence of strong singly ionized silicon features soon after explosion [13]. Most normal SNe Ia show an environment with no obvious CSM although it has been suggested that the presence of CSM dust could account for their abnormal extinction properties [14,15,16,17,18,19]. Any CSM around SNe Ia would be due to the mass loss from progenitor systems before the SN explosions.…”
Section: Introductionmentioning
confidence: 99%